Obliquity: Why Our Goals Are Best Achieved Indirectly - Kay, John (Penguin Books, 2010)
"John Kay tells a fast-paced detective story as he searches for the su rprising secret to success...Brilliant." -Tim Harford, author of The L ogic of Life In this revolutionary book, economist John Kay proves a n otion that feels at once paradoxical and deeply commonsensical: the be st way to achieve any complex or broadly defined goal, from happiness to preventing forest fires, is the indirect way. We can learn how to a chieve our objectives only through a gradual process of risk taking an d discovery-what Kay calls obliquity. The author traces this seemingly counterintuitive path to success as it manifests itself in nearly eve ry aspect of life, including business, politics, sports, and more.